EFFECT OF BIOFERTILIZER OF FORMULATION DOSE ON CHEMICAL PARAMETERS OF WATER QUALITY IN PEAT SOIL MEDIAS - Achmad Purnomo; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted from February to April 2018 at the Peat soil of Kualu Nenas Village, Kampar District, Riau Province. This study aims to determine the effect of formulation biofertilizer doses on changes in chemical parameters of water quality in peat soil ponds. The method used is the experimental method using a completely randomized design, one factor with fivetreatment levels and four replications. The treatments used were the formulated biofertilizer with a dose of P1 (70 g / m2), P2 (112.5 g / m2), P3 (150 g / m2), P4 (187.5 g / m2), and P0 (without formulationbiofertilizer). The results showed that the different of formulation of biofertilizer dose were significantly affected to chemical parameters of peat soil and water than dose of P4 (187.5 g / m2) was the best in this research. It was able to increase dose chemical parameters ie pH 4.70 - 6.60, organic content of soil 49.78 - 92.18%, N2O3 0.25 - 1.90%, P2O50.03 - 1.98%, K2O 0.07 - 2.43%, and C/N ratio 13.56 - 59.67 and, also the water chemical parameters was able to increase ie pH 5-7, DO 2.9 - 7.3 mg/l, CO2 13.48 - 29.96 mg/l, NO3 0.76 - 4.51 mg/l, and Orthophosphate 1.41 - 3.92 mg/l.Keyword: Peat Soil, Formulation Biofertilizer, Chemistry Parameters,